Cooking Recipe Rating Based on Sentiment Analysis - B. Sandhiya,; Sujetha.B,; Shneka. R, (International Journal of Psychosocial Rehabilitation, 2020)
Sentiment analysis of feedback on food recipe is to classify user responses to the positive or negative feedback on the food recipes. The suggested approach is appropriate by counting the polarity words on the food domain for evaluating feedback or opinions about food recipes. The aim of this research is to help users select the preferred recipes on online food commution from various food recipes. The program will rate the recipe, based on visitor feedback. So, it made finding the correct recipe simpler for people. With several people searching with online recipes this program would be helpful.Recipes you read obviously won't be the same as what you find after training. There are a number of inaccurate recipes you'll find online. Recipes must be rated by the user in order to cause the correct peoples. Here we propose a program that allows users to pick categories and post the recipes. Recipes are scored by the guests and commented on. So user will finish by finding a correct recipe.